2011
DOI: 10.2105/ajph.2010.300039
|View full text |Cite
|
Sign up to set email alerts
|

Community Stress, Psychosocial Hazards, and EPA Decision-Making in Communities Impacted by Chronic Technological Disasters

Abstract: Psychosocial stress has emerged as an important consideration in managing environmental health risks. Stress has adverse impacts on health and may interact with environmental hazards to increase health risk. This article's primary objective was to explore psychosocial stress related to environmental contamination. We hypothesized that knowledge about stress should be used in conjunction with chemical risk assessment to inform environmental risk management decisions. Knowledge of psychosocial stress at contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 61 publications
1
43
0
1
Order By: Relevance
“…Beyond biological plausibility, oil pollution and influence of exploration activities of oil industry in the rural communities could increase vulnerability including loss of livelihood and psychosocial stress [38] and [39]. For instance, loses incurred as a result of oil pollution of farmland, drinking water and fishing sources may have a knock-on effect to vulnerable individuals and families due to loss of occupational activities, income and leisure.…”
mentioning
confidence: 99%
“…Beyond biological plausibility, oil pollution and influence of exploration activities of oil industry in the rural communities could increase vulnerability including loss of livelihood and psychosocial stress [38] and [39]. For instance, loses incurred as a result of oil pollution of farmland, drinking water and fishing sources may have a knock-on effect to vulnerable individuals and families due to loss of occupational activities, income and leisure.…”
mentioning
confidence: 99%
“…This reflects prior studies which have found that targeted behavioral health interventions are largely unsuccessful when they do not address immediate environmental threats (Ory et al, 2002), lack of trust (Scammell et al, 2009), and otherwise incorporate local knowledge (Corburn, 2003). In this case as in others (Couch and Coles, 2011), the study process could exacerbate the physical and psychosocial health impacts on communities.…”
Section: Discussionmentioning
confidence: 71%
“…Few studies investigate the relationship between the perception of air pollution and disease outcomes (Gee and Takeuchi, 2004; Piro et al, 2008). We join others in calling for further research on “stress-intoxicant interactions” (Couch and Coles, 2011; McEwen and Tucker, 2011), which may assist in understanding and reducing health inequality.…”
Section: Discussionmentioning
confidence: 99%
“…A measure of oil spill stress was chosen based on research on technological disasters suggesting that chronic stress related to the uncertainty of financial, health and environmental risks, rather than direct impact only, may be most detrimental to mental health (Couch and Coles 2011). The measure has been used in recent prospective research showing significant effects of stress related to the Gulf Oil Spill on child and adolescent mental health ).…”
Section: Posttraumatic Stress Symptomsmentioning
confidence: 99%